2021
DOI: 10.3390/su131810102
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Watershed Hydrochemical Responses to Future Climate Changes Based on CMIP6 Scenarios in the Tianhe River (China)

Abstract: The impacts of future climate changes on watershed hydrochemical processes were assessed based on the newest Shared Socioeconomic Pathways (SSP) scenarios in Coupled Model Intercomparison Project Phase 6 (CMIP6) in the Tianhe River in the middle area of China. The monthly spatial downscaled outputs of General Circulation Models (GCMs) were used, and a new Python procedure was developed to batch pick up site-scale climate change information. A combined modeling approach was proposed to estimate the responses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 62 publications
0
3
1
Order By: Relevance
“…This means that the streamflow in the study area is more sensitive to future climate change in autumn and winter. The increasing trends of the annual TDN flux in this study area were lower than those in other similar areas (Sha et al 2021a). This was mainly due to the decrease of non-point source pollution loading resulting from the decrease in streamflow.…”
Section: Comparison With Other Similar Studies and Limitation Analysiscontrasting
confidence: 59%
See 2 more Smart Citations
“…This means that the streamflow in the study area is more sensitive to future climate change in autumn and winter. The increasing trends of the annual TDN flux in this study area were lower than those in other similar areas (Sha et al 2021a). This was mainly due to the decrease of non-point source pollution loading resulting from the decrease in streamflow.…”
Section: Comparison With Other Similar Studies and Limitation Analysiscontrasting
confidence: 59%
“…The decreasing trends of the annual streamflow in the study area were generally similar to those in other cases. However, under the best emission-controlled scenario of SSP1-26, other cases showed an increase in annual streamflow (Sunde et al 2018;Sha et al 2021a), but the current study area still showed a decreasing trend. This indicates that the study area is more sensitive to climate change.…”
Section: Comparison With Other Similar Studies and Limitation Analysismentioning
confidence: 62%
See 1 more Smart Citation
“…In climate change conditions, the Long-Ashton Research Station -Weather Generator (LARS-WG) meteorological data generation model is used for exponential downscaling and synthetic weather data generation. In other words, this model has been extensively used to estimate the basin's response to climate change (Sha et al, 2021). This model uses a semi-empirical series to calculate the length of dry and wet periods and generate synthetic data on temperature, precipitation, and solar radiation.…”
Section: The Lars-wg Modelmentioning
confidence: 99%